2012
DOI: 10.1128/aac.05636-11
|View full text |Cite
|
Sign up to set email alerts
|

Virologic Escape during Danoprevir (ITMN-191/RG7227) Monotherapy Is Hepatitis C Virus Subtype Dependent and Associated with R155K Substitution

Abstract: Danoprevir is a hepatitis C virus (HCV) NS3/4A protease inhibitor that promotes multi-log 10 reductions in HCV RNA when administered as a 14-day monotherapy to patients with genotype 1 chronic HCV. Of these patients, 14/37 experienced a continuous decline in HCV RNA, 13/37 a plateau, and 10/37 a rebound. The rebound and continuous-decline groups experienced similar median declines in HCV RNA through day 7, but their results diverged notably at day 14. Plateau group patients experienced a lesser, but sustained,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 36 publications
5
38
2
Order By: Relevance
“…Results showed that PSI-7977 was active in replicons with the NS3 R155K or D168V alteration. Consistent with previous findings (12,19,21), the R155K mutation was cross resistant to both RG7227 (a macrocyclic compound) and telaprevir (a linear ketoamide compound), while D168V conferred resistance only to RG7227 and not telaprevir. PSI-7977 also retained its activity against replicons with amino acid changes of NS3 C16S, A39V (resistant to the NS3/4A inhibitor ACH-806), or NS5A Y93H (resistant to the NS5A inhibitor BMS-790052).…”
Section: Genotype Coveragesupporting
confidence: 79%
See 1 more Smart Citation
“…Results showed that PSI-7977 was active in replicons with the NS3 R155K or D168V alteration. Consistent with previous findings (12,19,21), the R155K mutation was cross resistant to both RG7227 (a macrocyclic compound) and telaprevir (a linear ketoamide compound), while D168V conferred resistance only to RG7227 and not telaprevir. PSI-7977 also retained its activity against replicons with amino acid changes of NS3 C16S, A39V (resistant to the NS3/4A inhibitor ACH-806), or NS5A Y93H (resistant to the NS5A inhibitor BMS-790052).…”
Section: Genotype Coveragesupporting
confidence: 79%
“…PSI-7977 (prodrug of 2=-F-2=-C-methyluridine monophosphate) (38), PSI-352938 (prodrug of 2=-F-2=-C-methylguanosine monophosphate) (34), PSI-6130 (2=-F-2=-C-methylcytidine) (40), R1479 (4=-azidocytidine) (13), IDX-184 and INX-189 (prodrugs of 2=-C-meth-ylguanosine monophosphate) (43,48), NS5B nonnucleoside inhibitors NNI-1 (an indole analog), NNI-2 (a thiophene analog), NNI-3 (a benzothiadiazine analog), and HCV-796 (a benzofuran analog or NNI-4) (39), NS3 protease inhibitors telaprevir and RG7227 (ITMN-191) (21,22), NS3/4a inhibitor ACH-806 (46), and NS5A inhibitor BMS-790052 (8) were synthesized at Pharmasset and shown to be Ͼ95 to 99% pure by proton nuclear magnetic resonance, mass spectroscopy, and highperformance liquid chromatography analysis. Ribavirin was obtained from Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…The network identified an association between drug resistance mutation R155K (Bartels et al, 2008;Larrat et al, 2015;Lontok et al, 2015) and PI-exposure, suggesting this is a major mutation, while V36M is a minor drug resistance-associated variant, dependent also on the presence of R155K. These associations were confirmed in a separate HCV1a analysis, but no in the HCV1b analysis, probably due to R155K being less prevalent since two nucleotide substitutions (instead of one) are required in HCV1b patients (Lim et al, 2012). Cross-resistance between first-and second-generation PIs has been reported for this variant (Kieffer et al, 2012).…”
Section: Associations Between Ns3 Drug-resistance Variants and Pi-expsupporting
confidence: 61%
“…Substitutions NS3-V36A/M and NS3-T54A/S confer a low level of resistance to both Telaprevir and Boceprevir, and NS3-V170A/T to Boceprevir. There is also some cross-resistance of mutations in positions 36, 54 and 170 with other compounds, while changes in positions NS3-80, NS3-155 and NS3-168 are implicated in resistance to macrocyclic inhibitors [17,42] . Double mutants may also be selected by STAT-C treatments, combining two resistance mutations for the same or different PI class, with a potential for broad resistance to both linear and macrocyclic inhibitors [43] .…”
Section: Hcv Resistance To Ns3/4a Pismentioning
confidence: 99%
“…For instance, variations in NS3-V170 are present in most HCV genotype 1 isolates, and polymorphism in NS3-D168 is characteristic of HCV genotype 3 [32] . As the development of NS3/4A PIs was based in HCV genotype 1, subtype 1b, their antiviral activity with non-1b genotypes, may be not as effective, although some PIs inhibit more than one HCV genotype [22,42,[48][49][50] . Currently neither Boceprevir nor Telaprevir should be used in patients infected with HCV genotypes other than 1.…”
Section: Hcv Resistance To Ns3/4a Pismentioning
confidence: 99%